Effect of Seed and Fruit Position on Seed Quality in Ash Gourd (Benincasa hispida (Thunb.) Cogn.) - MURUGESAN. P; K. VANANGAMUDI (Seed Research, 2026)
Ash gourd seed crop was raised during July, 2002 to study the effect of fruit and seed position in the vine coupled with their maturity for getting quality seed. The results revealed that seeds from peduncle segment fruits produced low germination. The seeds, which are extracted from top, positioned fruits (46 and above node) outperformed middle (37-40th node) and bottom (27-30 node) positioned fruits in terms of seed germination. This study also confirmed that harvesting of fruits at 70 Days After Anthesis (DAA) was found to be correct and suitable stage for best seed quality in rainy season crop.